‘Thinking Through’ Games in the Classroom: Using Discursive Game Design to Play and Engage with Historical Datasets - Glas, René; van Vught, Jasper; Werning, Stefan (Transactions of the Digital Games Research Association, 2021)
In this contribution, we outline Discursive Game Design (DGD) as a practice-based educational framework, explain how to use this design framework to teach game historiography, and report on findings from a series of in-class experiments. Using Nandeck, a freely available software tool for card game prototyping, we created sets of playing cards based on two game-historical datasets. Students were then asked to prototype simple games with these card decks; both playtesting and co-creating each other’s games in an ongoing quasi-conversational process between different student groups fostered discussions on, and produced alternative insights into, the complex notion of (Dutch) game history, canonization/selection and games as national cultural heritage. The article shows how DGD can be implemented to allow for students with little or no design background to actively ‘think through’ games about the subject matter at hand.